2003
DOI: 10.1046/j.1523-1747.2003.12356.x
|View full text |Cite
|
Sign up to set email alerts
|

Mite Allergen Induces Allergic Dermatitis with Concomitant Neurogenic Inflammation in Mouse

Abstract: Pathogenesis of atopic dermatitis involved the interactions of immune and neuroendocrine systems. Here we describe a mouse model for atopic dermatitis with concomitant neurogenic inflammation, by epicutaneous sensitization with a dust mite allergen. Allergen patching resulted in localized dermatitis characterized by pronounced epidermal hyperplasia and spongiosis, which was associated with infiltration of eosinophils and neutrophils, degranulated mast cells, CD4+ and CD8+ T cells, and dendritic cells. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…Our data are reminiscent to previous studies in human AD showing that, although CD4 ϩ T cells predominated in AD skin lesions, T cells infiltrating the epidermis were almost exclusively CD8 ϩ T cells (12). Along these lines, studies in mouse models of AD reported that allergen challenge is associated with epidermal recruitment of CD8 ϩ T cells (25), which is dramatically enhanced by coexposure to the superantigen staphylococcal enterotoxin B (26). However, only a few CD8 ϩ T cells, compared with CD4 ϩ T cells, were detected in the skin in these studies probably because of the time at which T cell infiltration was analyzed.…”
Section: Discussionsupporting
confidence: 86%
“…Our data are reminiscent to previous studies in human AD showing that, although CD4 ϩ T cells predominated in AD skin lesions, T cells infiltrating the epidermis were almost exclusively CD8 ϩ T cells (12). Along these lines, studies in mouse models of AD reported that allergen challenge is associated with epidermal recruitment of CD8 ϩ T cells (25), which is dramatically enhanced by coexposure to the superantigen staphylococcal enterotoxin B (26). However, only a few CD8 ϩ T cells, compared with CD4 ϩ T cells, were detected in the skin in these studies probably because of the time at which T cell infiltration was analyzed.…”
Section: Discussionsupporting
confidence: 86%
“…HDM is a common allergen associated with human AD and bronchial asthma (4,40). In the present study, we demonstrated that HDM-treated mice exhibited phenotypes reminiscent of both acute and chronic AD lesions (Figure 1 and Supplemental Figures 1 and 2), as previously reported (27,28). In light of these prior reports, we here adopted HDM-sensitized mice as a representative mouse model of allergic skin inflammation.…”
Section: Discussionsupporting
confidence: 83%
“…However, in our HDM-sensitized mouse model, enhancement of IFN-γ expression in skin tissues was not observed, despite the appearance of other features of chronic AD skin lesions (Figure 1 and data not shown). Huang et al have also reported that skin lesions in HDM-treated mice do not show IFN-γ expression, whereas splenocytes responsive to allergen stimulation can induce IFN-γ production (28). Exposure to microbial products may make the difference between mouse models and patients (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that few CD8 ϩ T cells are found in the epidermis of AD patients but not in the epidermis of healthy controls (26). Furthermore, Huang et al (27) reported recently that epicutaneous exposure to mite allergen induces allergic dermatitis and the infiltration of few CD8 ϩ T cells into the epidermis. Similar with our OVA sensitization, both of these earlier observations show only few numbers of CD8 ϩ T cells in the epidermis.…”
Section: Figure 2 Immunohistochemical Analysis Of Cd3mentioning
confidence: 97%